TAVR Associated with Increased Late Mortality from Paravalvular Regurgitation - Buckley, Rita (MD Conference Express, 2012)
One-year data from the Placement of Aortic Transcatheter Valves Trial [PARTNER; NCT00530894] showed that survival rates were similar among high-risk patients with aortic stenosis who received either transcatheter aortic valve replacement or surgical replacement [Smith CR et al. N Engl J Med 2011; Vinall M. MD Conference Express: ACC 2011]. This article discusses outcomes after 2 years of follow-up in the PARTNER trial [Kodali SK et al. N Engl J Med 2012].